Advanced analysis of steel frames with effects of joint deformability and partial strength accounted for - Gizejowski, Marian A.; Branicki, Czeslaw J.; Barszcz, Anna M.; Krol, Pawel (Journal of Civil Engineering and Management, 2004)
The paper summarises the current progress in methods of advanced analysis for design of frames with semirigid joints. The methods presented in the paper belong to general second‐order refined plastic‐hinge methods that allow for the combined effects of joint stiffness degradation and distributed plasticity along the member length as well as across the member sections. The advanced analysis for steel frame design, proposed by the authors, is based on the spring‐in‐series model. The effect of joint semi‐rigidity and partial strength is taken care of by specifying certain values of the initial stiffness, ultimate moment and the shape factor of the moment‐rotation characteristic for the spring representing the joint. The effect of imperfections affecting the performance of imperfect structural members in compression is modelled by the application of a simplified tangent modulus concept combined with the reduction of the initial value of the elasticity modulus. The effect of residual stresses is taken care of by specifying certain values of the shape parameter for the moment‐rotation characteristic of the spring representing the gradual yielding of the member. It is dependent upon the cross‐section type and fabrication method (ie upon the residual stress pattern resulting from rolling or welding processes). A case study analysis is presented. Concluding remarks referring to the application of advanced analysis in design, pertaining to the study case considered, are drawn.First Published Online: 14 Oct 2010